Strategi Pengembangan Wisata Halal di Pulau Lombok - Taqy Muhammad Hirsalam; Dr. Asnita Frida Sebayang, S.E, M.Si. (UNISBA Press, 2023)
Abstract. One Thesis Title : Development of Halal Tourism Strategy on Lombok Island Lombok Island is one of the islands in West Nusa Tenggara Province which has a variety of superior tourism potential, such as cultural tourism, nature, to traditional arts. However, even though it has a lot of potential, Lombok Island still has several problems which are still homework for the local government in making Lombok Island a competitive halal tourism towards world- class tourism. This study aims to determine the strengths, weaknesses, opportunities and threats in developing halal tourism on Lombok Island and to find out how to develop halal tourism strategies on Lombok Island. The analytical method with a quantitative approach used in this study is SWOT analysis. The data used in this study were primary data obtained through questionnaires and interviews with halal tourism visitors and key informants. The results of this study indicate that there are 5 aspects of strengths and 2 aspects of weaknesses. 2 aspects of opportunities and 3 aspects of threats. The strengths and weaknesses are aspects of attractions, amenities, workforce/HR skills, accessibility, and supporting institutions. The strategy that can be carried out in developing halal tourism on Lombok Island is the S-0 (Strenght- Opportunity) strategy or a strategy that uses strength to take advantage of opportunities. The alternative S-O formulated is to optimize all internal and external aspects in repairing and building facilities and maintenance of halal tourism on Lombok Island as well as utilizing and improving various policies that have been issued by the government to support the development of halal tourism on Lombok Island. Abstrak. Strategi Pengembangan Wisata Halal di Pulau Lombok Pulau Lombok merupakan salah satu pulau di Provinsi Nusa Tenggara Barat yang memiliki potensi wisata unggulan yang beragam, seperti wisata kebudayaan, alam, hingga kesenian tradisional. Namun meskipun banyak potensi yang dimiliki, Pulau Lombok tetap memiliki beberapa permasalahn yang masih menjadi pekerjaan rumah bagi pemerintah daerah dalam menjadikan Pulau Lombok menjadi wisata halal yang berkompetitif menuju wisata berkelas dunia. penelitian ini bertujuan unutk mengetahui kekuata, kelemahan, peluang, dan ancaman dalam pengembangan wisata halal di Pulau Lombok serta untuk mengetahui bagaimana pengembangan strategi wisata halal di Pulau Lombok. Metode analisis dengan pendekatan kuantitatif yang dihunakan dalam penelitian ini adalah analisis SWOT. Data yang digunakan dalam penelitian ini data primer yang di dapat melalui penyebaran kuesioner maupun wawancara terhadap pengunjung wisata halal dan informan kunci. Hasil dari penelitian ini menunjukan terdapat 5 aspek kekuatan dan 2 aspek kelemahan. 2 aspek peluang dan 3 aspek ancaman. Adapun yang menjadi faktor kekuatan dan kelemahan yakni aspek atraksi, amenitas, keterampilan tenaga kerja/SDM, aksesibilitas, dan lembaga pendukung. Strategi yang dapat dilakukan dalam pengembangan wisata halal di Pulau Lombok adalah strategi S-0 (Strenght- Opportunity) atau strategi yang menggunakan kekuatan untuk memanfaatkan peluang. Alternative S-O yang dirumuskan adalah mengoptimalkan seluruh aspek internal dan eksternal dalam memperbaiki dan membangun sarana dan pemeliharaan wisata halal di Pulau Lombok serta memanfaatkan dan meningkatkan berbaga kebijakan yang telah dikeluarkan oleh pemerintah untuk mendukung perkembangan wisata halal di Pulau Lombok.